2013
DOI: 10.1371/journal.pone.0067758
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Krüppel-Like Factor 4 Facilitates Carcinogenesis by Inducing G1/S Phase Arrest in Clear Cell Renal Cell Carcinoma

Abstract: Krüppel-like factor 4 (KLF4) is a transcription factor with diverse functions in various cancer types; however, the function of KLF4 in clear cell renal cell carcinoma (ccRCC) carcinogenesis remains unknown. In this study, we initially examined KLF4 expression by using a cohort of surgically removed ccRCC specimens and cell lines. Results indicated that the transcription and translation of KLF4 were lower in ccRCC tissues than in patient-matched normal tissues. Furthermore, the KLF4 expression was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…4A). Others had previously demonstrated the presence of KLF 4 and KLF6 in proximal tubule cells [39, 40]. A review of the literature indicated that KLF8 in particular shared many functional attributes with HuR, including promotion of tumor development, growth, and metastasis, and a commonality of target genes [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). Others had previously demonstrated the presence of KLF 4 and KLF6 in proximal tubule cells [39, 40]. A review of the literature indicated that KLF8 in particular shared many functional attributes with HuR, including promotion of tumor development, growth, and metastasis, and a commonality of target genes [41].…”
Section: Resultsmentioning
confidence: 99%
“…Few KLF proteins have been characterized in proximal tubules. One example is KLF4, which functions as a tumor suppressor in a number of tissues, and was recently shown to be expressed in proximal tubule cells and downregulated in renal cell carcinoma tissues [40]. Additionally, in a screen for mRNAs that are upregulated in the earliest stages of renal ischemia/reperfusion injury, KLF6 (formerly Zf9) was detected.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 All human tissues and xenograft tumor tissues were fixed in 10% neutral formalin and embedded in paraffin. 21,22 All human tissues and xenograft tumor tissues were fixed in 10% neutral formalin and embedded in paraffin.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…These SNPs may affect mRNA stability or alter the binding of transcription factors to the promoter regions of GRHL genes (Table ). Of these, KLF4 (Krüppel‐like factor 4) is a potential suppressor of ccRCC . There is also evidence pointing to the involvement of STAT4 (signal transducer and activator of transcription 4) and STAT5A/B in ccRCC .…”
Section: Discussionmentioning
confidence: 99%